Environmental tax and its role in sustainable social development (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:  The research aims to diagnose the relationship between the environmental tax and the development of the sustainable social dimension, where the environmental tax is considered a tool in promoting sustainable development according to its economic, social and environmental dimensions through the application of legislation and instructions for environmental protection, and that imposing an environmental tax will have a clear impact in achieving the dimensions of sustainable development and compliance With regard to the social dimension, the research relied on the financial data for the years (2019-2022) in obtaining information. The research reached a set of results, the most prominent of which was that the imposition of environmental tax contributes greatly to the promotion of sustainable development in its various dimensions, as it reduces the rates of environmental pollution, and eliminates Poverty and unemployment, so work is required to amend the tax law and include an article on environmental tax.